2014
DOI: 10.1002/adma.201304756
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State Supercapacitor Based on Activated Carbon Cloths Exhibits Excellent Rate Capability

Abstract: Activated carbon cloth is used as an electrode, achieving an excellent areal capacitance of 88 mF/cm(2) (8.8 mF/g) without the use of any other capacitive materials. Significantly, when it is incorporated as part of a symmetric solid-state supercapacitor device, a remarkable charge/discharge rate capability is observed; 50% of the capacitance is retained when the charging rate increases from 10 to 10,000 mV/s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
409
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 695 publications
(437 citation statements)
references
References 38 publications
23
409
2
3
Order By: Relevance
“…Various carbon-based materials have been investigated experimentally and theoretically as electrode materials for energy storage and conversion devices such as in fuel cells [60][61][62][63][64] , supercapacitors (SCs) [65][66][67][68][69][70] and LIBs [71][72][73][74][75], all aimed at improving the specific capacity, cyclic efficiency, lifetime, power and energy density of the energy storage devices [71,76]. The electrochemical insertion of sodium ion in carbon based materials started in the 1980's.…”
Section: Hard Carbonmentioning
confidence: 99%
“…Various carbon-based materials have been investigated experimentally and theoretically as electrode materials for energy storage and conversion devices such as in fuel cells [60][61][62][63][64] , supercapacitors (SCs) [65][66][67][68][69][70] and LIBs [71][72][73][74][75], all aimed at improving the specific capacity, cyclic efficiency, lifetime, power and energy density of the energy storage devices [71,76]. The electrochemical insertion of sodium ion in carbon based materials started in the 1980's.…”
Section: Hard Carbonmentioning
confidence: 99%
“…Since carbon cloths are made of carbon fiber yarns, which are closely packed together and lack of mesopores,22 it makes them impenetrable for bacteria. On the contrary, bacterial colonies were clearly observed on both the exterior and interior parts of rGO‐Ni and N‐GA anodes (Figure 4b,c).…”
Section: Resultsmentioning
confidence: 99%
“…11-16 Wang et al 17,18 reported the chemical and electrochemical exfoliation approach by using acidic solutions to enhance the capacitance of the CC. In their approach, the surface area of the CC was increased but large number of oxygen containing functional * Electrochemical Society Member.…”
Section: -9mentioning
confidence: 99%